2004
DOI: 10.1007/s10144-004-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental investment and family dynamics: interactions between theory and empirical tests

Abstract: The pattern of parental investment (PI) seen in nature is a product of the simultaneous resolution of conflicts of interest between the members of a family. How these conflicts are resolved depends upon the mating system, the genetic mechanism, on whether extra PI affects current or future offspring, and the behavioural mechanisms underlying supply and demand of PI. Until recently very little empirical work has been done to underpin these key determinants of conflict resolution. This review examines recent emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 71 publications
(114 reference statements)
2
42
0
1
Order By: Relevance
“…Both predictor variables (gender and breeding status) are categorical, hence the parameters represent effect sizes. and offspring (survival, fitness; Royle et al 2004). We therefore had expected that, due to a trade-off between the amount of time allocated to different activities such as selfprovisioning, chick provisioning, and chick care, certain characteristics of foraging behaviour would change in the course of a season.…”
Section: Discussionmentioning
confidence: 99%
“…Both predictor variables (gender and breeding status) are categorical, hence the parameters represent effect sizes. and offspring (survival, fitness; Royle et al 2004). We therefore had expected that, due to a trade-off between the amount of time allocated to different activities such as selfprovisioning, chick provisioning, and chick care, certain characteristics of foraging behaviour would change in the course of a season.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of conflict between individuals, and between sets of genes, are difficult to predict, but may include stable equilibria, tugs-or-war over resource allocation, one party 'winning' due to asymmetries in control over resource allocation, or continued conflict (e. g., Royle et al 2004;Smiseth et al 2008). Conflicts such as genomic imprinting also potentiate liability to phenotypes associated with disease (Crespi 2010), due to functional haploidy of imprinted genes, dysregulation of tug-of-war based systems that evolved in this context, and the expected general higher lability of epigenetic gene-expression control systems (based on methylation and histone modifications) compared to the lability of DNA alterations via mutation.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of energy that an offspring demands is often greater than the female's optimal level of supply. Early studies of parent-offspring conflict assumed or concluded that parents controlled energy allocation, but more recent studies suggest that offspring have a greater influence on demand than previously suspected (Gentry and Holt 1986;Royle et al 2004). Factors such as offspring size may influence energy allocation because larger offspring will be able to consume and process more milk and may therefore have greater demand.…”
Section: Dynamic Influence Of Maternal and Pup Traits On Maternal Carmentioning
confidence: 99%